PERCEIVED ENJOYMENT OF MOBILE MATHEMATICAL LEARNING GAMES - Venter, Marisa (UNISA: ISTE Conference Mathematics, Science and Technology Education, 2016)
Perceived enjoyment is often reckoned as one of the most important factors influencing consumer behavior in educational learning material. Without the educational application providing a positive experience, children are unlikely to interact with it. Previous research on the use of educational applications in mathematics education has focused primarily on the learning potential of these applications and has not adequately addressed the perceived enjoyment. The purpose of this paper is to address this gap and to investigate the perceived enjoyment of mobile mathematical learning games. This study adopted the GameFlow model and Game-Based Learning model as theoretical base. A mixed method research methodology was employed where qualitative and quantitative data was gathered through surveys and semi-structured interviews. Twenty-six children, aged 10 to 13, from selected schools in one of South Africa’s provinces, participated in the study. The results indicate that the interest, fantasy, sensation and goal constructs, as well as the reward systems of mobile mathematical learning games, were most influential in terms of perceived enjoyment. The findings of this study could be used by educators and parents in the evaluation and selection of mobile mathematical learning games.
Conference Proceedings
Keywords: Perceived enjoyment; Mathematical applications; Educational applications; Primary school learners